A wolf in sheep’s clothing: concomitant appendicitis with occult cecal adenocarcinoma - Mejia, Jonathan; Haj, Roland; Nithisoontorn, Sutasinee; Louis, Martine A.; Mandava, Nageswara (International Surgery Journal, 2021)
We present the case of an 89-years-old female with an atypical presentation of an obstructive acute appendicitis secondary to a cecal carcinoma. The physical exam revealed a distended abdomen with bilateral lower quadrants tenderness without rebound or rigidity. CT scan demonstrated distal small bowel obstruction and ruptured acute appendicitis. Patient was treated conservatively with nasogastric decompression, intravenous fluids, and antibiotics. She later underwent CT guided drainage of a rim-enhancing fluid collection and her symptoms eventually resolved. She returned a week later and a CT imaging showed high grade distal small bowel obstruction, and findings were a 4.5 cm diameter cecal mass. She underwent an exploratory laparotomy and modified right hemicolectomy with ileostomy for. She had an uneventful postoperative course. Pathology revealed poorly differentiated adenocarcinoma of the cecum stage III T4N1Mx. Appendectomy for appendicitis is the most commonly performed emergency operation in the world. Appendicitis are often rare in elderly, with atypical or delayed presentation and expanded differential diagnosis, making preoperative diagnosis challenging. With the increase overall risk of cancer in this age group, occult colonic carcinoma should be high in the differential diagnosis. Three mechanisms potentially leading to obstruction of the appendiceal lumen by the tumor includes: immediate proximity to the lumen, inflammatory changes from the tumor, back pressure on the cecum causing obstruction of the appendix. Despite advances in imaging, local inflammation, collections, and masses may be misleading. The diagnostic accuracy of CT scan reportedly can be as low as 54% for cecal tumors.